2015
DOI: 10.1177/0022146515582099
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations among Discordant Sexual Orientation Dimensions and Hazardous Drinking in a Cohort of Sexual Minority Women

Abstract: We examined differences between sexual minority women’s (SMW’s) sexual identity and sexual behavior or sexual attraction as potential contributors to hazardous drinking across a 10-year period. Data are from a longitudinal study examining drinking and drinking-related problems in a diverse, community-based sample of self-identified SMW (Wave 1: n = 447; Wave 2: n = 384; Wave 3: n = 354). Longitudinal cross-lagged models showed that SMW who report higher levels of identity-behavior or identity-attraction discor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 68 publications
2
55
0
1
Order By: Relevance
“…For example, Parks (1999) reported that some lesbian, bisexual and queer women consume alcohol in the context of identity conflict, particularly when attempting to live in both heterosexual and lesbian, bisexual and queer communities, while for others it is a response to internalised homophobia and identity confusion (Herrick et al 2013). Further, for some women, identity influences may provide an explanation for the higher levels of risky drinking amongst bisexual women compared with lesbian women, as previously reported (Hughes, Szalacha, and McNair 2015;Talley et al 2015). Non-lesbian identities can be marginalised even within lesbian, bisexual and queer communities, leading to a further need for coping mechanisms such as heavy alcohol use (Schauer, Berg, and Bryant 2013).…”
Section: Discussionmentioning
confidence: 69%
“…For example, Parks (1999) reported that some lesbian, bisexual and queer women consume alcohol in the context of identity conflict, particularly when attempting to live in both heterosexual and lesbian, bisexual and queer communities, while for others it is a response to internalised homophobia and identity confusion (Herrick et al 2013). Further, for some women, identity influences may provide an explanation for the higher levels of risky drinking amongst bisexual women compared with lesbian women, as previously reported (Hughes, Szalacha, and McNair 2015;Talley et al 2015). Non-lesbian identities can be marginalised even within lesbian, bisexual and queer communities, leading to a further need for coping mechanisms such as heavy alcohol use (Schauer, Berg, and Bryant 2013).…”
Section: Discussionmentioning
confidence: 69%
“…Because SMW are more likely than their heterosexual counterparts to report sexual victimization, 47,48 it is quite possible that some of the reported unintended pregnancies were the result of coerced sexual experiences. However, given findings from other studies that show high levels of identity behavior incongruence and sexual fluidity among SMW, 35,39,41,42 many of these pregnancies likely resulted from consensual sexual relationships with men.…”
Section: Discussionmentioning
confidence: 94%
“…Heavy episodic drinking was assessed using a question that asked about frequency in the past 12 months of consuming six or more drinks in a day. 39,54,56,57 Participants are coded as 1 if they reported at least one heavy episodic drinking episode in the last 12 months and 0 if they did not. A similar question asked about frequency of subjective intoxication (''drinking enough to feel drunk-where drinking noticeably affected your thinking, talking, and behavior'').…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Discordance between these multiple dimensions of sexual orientation has been documented to be an important health determinant itself. [10][11][12][13][14] While researchers have interpreted the Statistics Canada question to measure sexual identity, [2][3][4][5] it is still unclear if respondents actually interpret the question in this way, given that the measure defines these categories behaviourally, e.g., "bisexual (sexual relations with both sexes)". Furthermore, it is unknown how trans and non-binary persons who may not identify as strictly male or female may understand such a question, as the concepts of "opposite sex" or "same sex" may not make sense.…”
mentioning
confidence: 99%